A Dermocosmetic Significantly Reduces the Frequency and Intensity of Facial Skin Intolerability and Sensitivity in Subjects with Skin Intolerant to Skin Care Products and Sensitive Skin [Corrigendum] - Kerob D; Czermanska A; Karamon EM; Moga A; Lecerf G; Nioré M; Le Dantec G; Le Floc'h C; Tan J (Dove Medical Press, 2023)
Kerob D, Czermanska A, Karamon EM, et al. Clin Cosmet Investig Dermatol. 2023;16:1787–1794. The authors have advised Figure 5b on page 1792 is incorrect. Due to an error that occurred inadvertently at the time of figure assembly, figure part b was duplicated from part a. The correct Figure 5 is shown below. Figure 5 Biomarkers at Day 0 and Day 14. (a) Interleukin 1α. (b) Interleukin-1-receptor antagonist. (c) Prostaglandin E2. Differences from Day 0 were statistically significant (*p<0.0001) for all 3 biomarkers after 14 days of daily use. The authors apologize for this error and advise it does not affect the results of the paper.